A case report of Vancomycin in the treatment of Q fever endocarditis - Wang, Xuan; Zou, Guangmei; Wang, Qianli; Li, Jiao (Frontiers in Cellular and Infection Microbiology, 2024)
The patient, a 43 year-old male, was admitted to the hospital with gradually aggravated exertional palpitations and chest tightness over a 2-day period. Upon hospital admission, a cardiac ultrasound revealed aortic valve redundancy, however multiple blood culture investigations came back negative. Blood mNGS was perfected, revealing Coxiella burnetii, and the diagnosis of Q fever (query fever) was established. The temperature and inflammatory indices of the patient were all normal with the treatment of vancomycin before cardiac surgery. But for the potential liver damage of and the Coxiella burnetii was still positive in the anti-phase II IgG titer, the doxycycline and hydroxychloroquine instead of vancomycin were applied for the patient. Despite receiving standardized anti-infective therapy of doxycycline combined with hydroxychloroquine, this patient had fever and increased leukocytes following surgery. After the addition of vancomycin as an anti-infective treatment, the temperature and leukocytes improved quickly. During the treatment of vancomycin, a discovery of liver injury may have resulted. These findings provide new therapy options for future professionals.